Women's health status in urban Ghana: Dimensions and differentials using short form 36 - Frempong-Ainguah, F.; Bailey, C.E.; Hill, A.G. (BioMed Central Ltd., 2018)
Background: Global discourse on population, health and development have placed women's health issues at the top of development agenda. Women's reproductive health has received some attention in Ghana since the mid-1990s. However, studies on women's general health status, dimensions and the differentials in a rapidly growing urban setting is poorly understood and under-researched. This study sought to examine the various pathways in which individual socio-demographic factors, economic characteristics and endowment influence self-assessed health status among women living in the city of Accra, Ghana. Methods: The paper draws on a cross-sectional study carried out in 2008 and 2009 using a representative sample of urban women 20 years and older (n=2814). Multivariate stepwise linear regression models were performed to investigate the influence of socio-demographic, economic and health indicators on health-related quality of life, measured by eight sub-scales of the Short Form-36 (SF-36). Interaction effects between some demographic and socio-economic variables were also performed. Results: The analyses show diverse relationships between demographic, socio-economic and health indicators and health outcomes assessed using eight SF-36 sub-scales. Education, disease symptoms and age of the respondent were the most significant factors influencing good overall health status. Interestingly, age has no significant effect on mental health after controlling for all other explanatory variables. Conclusions: The findings show that health issues are multi-faceted requiring socio-cultural, health and economic policy interventions. Investing in women's education is important to improve health status. There is also the need for more effective collaboration across various sectors to improve the health and well-being of women in general. Ageing has increasing relationship with poor physical health status and the elderly should be given needed attention and support. © 2018 The Author(s).
Keywords: Short Form-36 eight scales; Socio-demographic differentials; Women's health